Lanthanum-aluminum single crystal as well as preparation method and application thereof

By controlling the crystal growth conditions of the lanthanum rhenium single crystal under vacuum environment and using excessive Al flux and post-treatment technology, the problem of difficulty in producing high-quality topological material single crystals in the prior art is solved, and a lanthanum rhenium single crystal with high crystal quality, large size and giant magnetoresistive effect is achieved.

CN119843367AActive Publication Date: 2025-04-18NINGBO UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510315113.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

It is difficult to produce high-quality single crystals of topological materials in the prior art, especially while maintaining the huge magnetoresistive effect, ensuring high crystal quality and large-size single crystals are difficult to achieve.

Method used

By performing crystal growth of lanthanum aluminum single crystal under vacuum, the temperature, time and cooling rate of crystal growth are controlled, and excessive Al is used as flux to avoid the introduction of impurities. Finally, impurities are removed and the quality of the single crystal is improved through post-treatment such as centrifugation and quenching.

Benefits of technology

It has achieved high crystallization quality and large size of lanthanum aluminum single crystal, with huge magnetoresistance and high residual resistivity, meeting the needs of high-quality and large-size topological materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843367A_ABST
    Figure CN119843367A_ABST
Patent Text Reader

Abstract

The invention provides a lanthanum-aluminum single crystal as well as a preparation method and application thereof, and belongs to the technical field of topological materials. In the lanthanum-aluminum single crystal provided by the invention, the molar ratio of lanthanum to aluminum is 3: (11-11.8), the residual resistivity of the lanthanum-aluminum single crystal is greater than or equal to 100, and the magnetic resistance of the lanthanum-aluminum single crystal at 2K is greater than or equal to 3000%. The molar ratio of the lanthanum-aluminum single crystal provided by the invention is very close to the ideal value 3: 11 of a La3Al11 single crystal, the lanthanum-aluminum single crystal not only has high residual resistivity and huge magnetic resistance, but also has very high crystal quality and large size, and the length of the lanthanum-aluminum single crystal can reach 5mm, so that the requirements on topological materials with high crystal quality and large size can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of topological materials, and in particular to a lanthanum aluminum single crystal and a preparation method and application thereof. Background Art

[0002] Topological materials refer to materials whose electronic states have topological properties. The electronic structure of these materials remains unchanged under certain transformations. This invariance stems from the special combination of the geometric structure of the material and the interaction between electrons. Topological materials have a variety of macroscopic quantum effects, such as the significant giant magnetoresistance effect. The resistance of topological materials will change greatly when the magnetic field changes. This property has brought new breakthrough opportunities for ultra-high density storage and sensor technology. The anomalous Hall and anomalous Nernst effects break the conventional laws of traditional Hall and Nernst effects and provide unique ideas for the design of new electronic devices. There is also the negative magnetoresistance effect caused by chiral anomalies. This peculiar phenomenon of reduced resistance in a magnetic field has immeasurable potential application value in cutting-edge scientific and technological fields such as quantum computing and quantum communication.

[0003] To deeply study and reveal the topological properties and potential application value of topological materials, the first problem that needs to be solved is how to produce high-quality single crystals of topological materials. High-quality single crystals of topological materials are not only the basis and prerequisite for studying topological properties, but also the most critical and important link in the entire research process. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a lanthanum aluminum single crystal and a preparation method and application thereof. The lanthanum aluminum single crystal has high crystal quality and large size and exhibits a giant magnetoresistance effect.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a lanthanum aluminum single crystal, wherein the molar ratio of lanthanum to aluminum in the lanthanum aluminum single crystal is 3:(11-11.8), the residual resistivity of the lanthanum aluminum single crystal is ≥100, and the magnetic resistance of the lanthanum aluminum single crystal at 2K is ≥3000%.

[0006] The molar ratio of lanthanum to aluminum in the lanthanum aluminum single crystal provided by the present invention is 3: (11-11.8), which is very close to La3Al 11 The ideal value of the single crystal is 3:11. The lanthanum aluminum single crystal not only has high residual resistivity and huge magnetic resistance, but also has very high crystal quality and large size. The length of the lanthanum aluminum single crystal can reach 5 mm, which can meet the needs of high crystal quality and large size topological materials.

[0007] In a possible implementation manner, the length of the lanthanum aluminum single crystal is ≥0.1 mm.

[0008] Furthermore, the residual resistivity of the lanthanum aluminum single crystal is ≥235.

[0009] Furthermore, the magnetoresistance of the lanthanum aluminum single crystal at 2K is ≥8000%.

[0010] In a possible implementation, the magnetic susceptibility of the lanthanum aluminum single crystal at 2K exhibits a quantum oscillation effect.

[0011] In a second aspect, the present invention provides a method for preparing the above-mentioned lanthanum aluminum single crystal, comprising the following steps: S1. Weighing raw materials: weighing lanthanum and aluminum under a protective atmosphere, mixing them to obtain a mixed raw material, wherein the molar ratio of the lanthanum to the aluminum is ≤1:10; S2, crystal growth: the mixed raw material in step S1 is subjected to crystal growth under a vacuum environment, the insulation temperature of the crystal growth is 900-1200°C, the insulation time is more than 1200 min, and after the insulation is completed, the temperature is lowered at a cooling rate of ≤3.5°C / h to obtain a lanthanum aluminum solution; S3, post-processing: the lanthanum aluminum solution in step S2 is post-processed to obtain lanthanum aluminum single crystals.

[0012] The preparation method of the lanthanum aluminum single crystal provided by the present invention adopts excessive Al as a flux. Since Al is one of the components of the lanthanum aluminum single crystal, the introduction of impurities into the single crystal due to the addition of other fluxes is avoided, which is conducive to obtaining high-quality lanthanum aluminum single crystals; by controlling the temperature, time and cooling rate of crystal growth, more defects are avoided during the crystal growth process, which is conducive to obtaining lanthanum aluminum single crystals with fewer defects and high quality; the lanthanum aluminum single crystals are separated from the aluminum solution through post-processing, and the Al flux attached to the surface of the lanthanum aluminum single crystals is removed to obtain high-quality lanthanum aluminum single crystals.

[0013] In a possible implementation, the process of weighing the raw materials in step S1 is performed in a glove box. In the glove box, on the one hand, it is convenient to form a space with a protective atmosphere, and on the other hand, it is also convenient to perform weighing operations under the protective atmosphere.

[0014] In a possible implementation manner, the protective atmosphere in step S1 is at least one of nitrogen and argon.

[0015] In a possible implementation, the molar ratio of the lanthanum to the aluminum in step S1 is 1:(11-15). By controlling the molar ratio of lanthanum to aluminum within the range of 1:(11-15), the growth temperature of the lanthanum aluminum single crystal can be reduced while ensuring the acquisition of high-quality lanthanum aluminum single crystals, which is conducive to growing high-quality lanthanum aluminum single crystals at a relatively low temperature.

[0016] In a possible implementation, the specific process of step S1 is: in a glove box with a protective atmosphere, the lanthanum and the aluminum are weighed according to the molar ratio and placed in a container, after the lanthanum and the aluminum are evenly mixed, the outlet of the container is plugged with quartz wool, and the container is taken out of the glove box.

[0017] In a possible implementation, the time for the mixed raw material to be heated from room temperature to the insulation temperature in step S2 is 800-1200 min. By controlling the heating time, the mixed raw material is slowly heated to the temperature required for crystal growth, avoiding uneven heating of the mixed raw material due to too fast heating.

[0018] In a possible implementation, the cooling process in step S2 adopts one-step cooling or step-by-step cooling.

[0019] Furthermore, the one-step cooling process is to cool the temperature to 700-800° C. at a cooling rate of ≤3.5° C. / h. The one-step cooling method has a simpler process and is more conducive to the crystal growth of lanthanum aluminum single crystals by controlling the cooling rate and the cooling temperature.

[0020] Furthermore, the step-by-step cooling process is to cool down to 900-950°C at a cooling rate of ≤3°C / h, then increase the temperature to 1100-1150°C at a heating rate of 3-5°C / min, and then cool down to 700-800°C at a cooling rate of ≤3°C / h. By adopting the above-mentioned step-by-step cooling method, it is more conducive to the growth of lanthanum aluminum single crystals and is conducive to further improving the magnetoresistance and residual resistivity of lanthanum aluminum single crystals.

[0021] In a possible embodiment, the process of forming the vacuum environment in step S2 is: placing the mixed raw material in step S1 in a closed container with a protective atmosphere, extracting the protective gas in the closed container, and using a high-temperature flame in conjunction with a vacuum pump to vacuum-pack the mixed raw material in the closed container.

[0022] In a possible implementation manner, the post-treatment in step S3 includes centrifugal treatment, quenching and flux removal.

[0023] Furthermore, the temperature of the centrifugal treatment is 700-800°C.

[0024] Furthermore, the rotation speed of the centrifugal treatment is ≥2500 r / min.

[0025] Furthermore, the flux removal uses a sodium hydroxide solution.

[0026] In a third aspect, the present invention also provides applications of the above-mentioned lanthanum aluminum single crystal in the fields of storage, sensors, quantum computing or quantum communication.

[0027] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0028] The reagents and raw materials used in the present invention are commercially available.

[0029] The positive and progressive effects of the present invention are: The lanthanum aluminum single crystal provided by the present invention not only has high residual resistivity and huge magnetic resistance, but also has very high crystal quality and large size. The length of the lanthanum aluminum single crystal can reach 5 mm, which can meet the demand for high-quality and large-size topological materials and enrich the topological material research system. The preparation method of the lanthanum aluminum single crystal provided by the present invention is not only simple and convenient to operate, but also very easy to form high-quality lanthanum aluminum single crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the powder X-ray diffraction (XRD) pattern of the lanthanum aluminum single crystal prepared in Example 1.

[0031] Figure 2 This is a microscope image of the lanthanum aluminum single crystal prepared in Example 1.

[0032] Figure 3 Elemental energy spectrum (EDS) of the lanthanum aluminum single crystal prepared in Example 1 and a microscope image of the scanning area.

[0033] Figure 4 The resistivity of the lanthanum aluminum single crystal prepared in Example 1 and Example 2 varies with temperature.

[0034] Figure 5 Graph showing the change in magnetic resistance of the lanthanum aluminum single crystal prepared in Example 1 and Example 2 at 2 K as a function of magnetic field.

[0035] Figure 6 Graph showing the change in magnetic susceptibility of the lanthanum aluminum single crystal prepared in Example 1 and Example 2 at 2 K as a function of magnetic field. DETAILED DESCRIPTION

[0036] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0037] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0038] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0039] Example 1

[0040] This embodiment provides a lanthanum aluminum single crystal, which is prepared by the following method: S1. Weighing raw materials: In a glove box filled with nitrogen, weigh lanthanum and aluminum in a molar ratio of 1:13 and place them in a crucible. After the lanthanum and aluminum are evenly mixed, place the crucible in a quartz tube, plug quartz wool into the outlet of the quartz tube, and then take the quartz tube out of the glove box; S2, crystal growth: installing the quartz tube taken out in step S1 on a vacuum packaging device, extracting nitrogen from the inside of the quartz tube, and vacuum packaging the quartz tube using a hydrogen-oxygen machine; placing the vacuum-packaged quartz tube in a muffle furnace, heating for 1200 min to raise the temperature in the muffle furnace from room temperature to 1200 ° C, then keeping it at 1200 ° C for 1480 min, then cooling it to 950 ° C at a cooling rate of 2 ° C / h, then heating it to 1150 ° C at 5 ° C / min, then cooling it to 800 ° C at a cooling rate of 1 ° C / h, and keeping it at 800 ° C to obtain a lanthanum aluminum solution in the quartz tube; S3, post-treatment: after the quartz tube cooled to 800 ° C in step S2 is taken out from the muffle furnace, it is inverted in a centrifuge and centrifuged for 10 s at a centrifuge speed of 2500 r / min, and then the quartz tube is quickly placed in cold water for quenching; the quartz tube is opened to take out the lanthanum aluminum single crystal with metallic luster, and the lanthanum aluminum single crystal is soaked in a diluted sodium hydroxide solution to remove impurities on its surface to obtain a high-quality lanthanum aluminum single crystal, which is recorded as sample 1.

[0041] Example 2

[0042] This embodiment provides a lanthanum aluminum single crystal, which is prepared by the following method: S1. Weighing raw materials: In a glove box filled with nitrogen, weigh lanthanum and aluminum in a molar ratio of 1:13 and place them in a crucible. After the lanthanum and aluminum are evenly mixed, place the crucible in a quartz tube, plug quartz wool into the outlet of the quartz tube, and then take the quartz tube out of the glove box; S2, crystal growth: installing the quartz tube taken out in step S1 on a vacuum packaging device, extracting nitrogen from the inside of the quartz tube, and vacuum packaging the quartz tube using a hydrogen-oxygen machine; placing the vacuum-packaged quartz tube in a muffle furnace, heating it for 1000 min to raise the temperature in the muffle furnace from room temperature to 1100 ° C, then keeping it at 1100 ° C for 1440 min, and then cooling it to 700 ° C at a cooling rate of 3 ° C / h, and obtaining a lanthanum aluminum solution in the quartz tube; S3, post-processing: after the quartz tube cooled to 700°C in step S2 is taken out from the muffle furnace, it is inverted in a centrifuge and centrifuged for 2 min, and then the quartz tube is taken out from the centrifuge after it cools to room temperature; the quartz tube is opened to take out the lanthanum aluminum single crystal with metallic luster, and the lanthanum aluminum single crystal is soaked in a diluted sodium hydroxide solution to remove impurities on its surface to obtain high-quality lanthanum aluminum single crystal, which is recorded as sample 2.

[0043] Example 3

[0044] This embodiment provides a lanthanum aluminum single crystal, which is prepared by the following method: S1. Weighing raw materials: In a glove box filled with nitrogen, weigh lanthanum and aluminum in a molar ratio of 1:15 and place them in a crucible. After the lanthanum and aluminum are evenly mixed, place the crucible in a quartz tube, plug quartz wool into the outlet of the quartz tube, and then take the quartz tube out of the glove box; S2, crystal growth: installing the quartz tube taken out in step S1 on a vacuum packaging device, extracting nitrogen from the inside of the quartz tube, and vacuum packaging the quartz tube using a hydrogen-oxygen machine; placing the vacuum-packaged quartz tube in a muffle furnace, heating for 1200 min to raise the temperature in the muffle furnace from room temperature to 1200 ° C, then keeping it at 1200 ° C for 1480 min, and then cooling it down to 750 ° C at a cooling rate of 2 ° C / h, and obtaining a lanthanum aluminum solution in the quartz tube; S3, post-processing: after the quartz tube cooled to 750°C in step S2 is taken out from the muffle furnace, it is inverted in a centrifuge and centrifuged for 3 min, and then the quartz tube is taken out from the centrifuge after it cools to room temperature; the quartz tube is opened to take out the lanthanum aluminum single crystal with metallic luster, and the lanthanum aluminum single crystal is soaked in a diluted sodium hydroxide solution to remove impurities on its surface to obtain high-quality lanthanum aluminum single crystal, which is recorded as sample 3.

[0045] Example 4

[0046] This embodiment provides a lanthanum aluminum single crystal, which is prepared by the following method: S1. Weighing raw materials: In a glove box filled with nitrogen, weigh lanthanum and aluminum in a molar ratio of 1:10 and place them in a crucible. After the lanthanum and aluminum are evenly mixed, place the crucible in a quartz tube, plug quartz wool into the outlet of the quartz tube, and then take the quartz tube out of the glove box; S2, crystal growth: installing the quartz tube taken out in step S1 on a vacuum packaging device, extracting nitrogen from the inside of the quartz tube, and vacuum packaging the quartz tube using a hydrogen-oxygen machine; placing the vacuum-packaged quartz tube in a muffle furnace, heating for 800 minutes to raise the temperature in the muffle furnace from room temperature to 900°C, then keeping it at 900°C for 1580 minutes, and then cooling it down to 800°C at a cooling rate of 3°C / h, and obtaining a lanthanum-aluminum solution in the quartz tube; S3, post-processing: after the quartz tube cooled to 800°C in step S2 is taken out from the muffle furnace, it is inverted in a centrifuge and centrifuged for 4 min, and then the quartz tube is taken out from the centrifuge after it cools to room temperature; the quartz tube is opened to take out the lanthanum aluminum single crystal with metallic luster, and the lanthanum aluminum single crystal is soaked in a diluted sodium hydroxide solution to remove impurities on its surface to obtain high-quality lanthanum aluminum single crystal, which is recorded as sample 4.

[0047] Example 5

[0048] This embodiment provides a lanthanum aluminum single crystal, which is prepared by the following method: S1. Weighing raw materials: In a glove box filled with nitrogen, weigh lanthanum and aluminum in a molar ratio of 1:12 and place them in a crucible. After the lanthanum and aluminum are evenly mixed, place the crucible in a quartz tube, plug quartz wool into the outlet of the quartz tube, and then take the quartz tube out of the glove box; S2, crystal growth: installing the quartz tube taken out in step S1 on a vacuum packaging device, extracting nitrogen from the inside of the quartz tube, and vacuum packaging the quartz tube using a hydrogen-oxygen machine; placing the vacuum-packaged quartz tube in a muffle furnace, heating it for 1100 minutes to raise the temperature in the muffle furnace from room temperature to 1000°C, then keeping it at 1000°C for 1350 minutes, and then cooling it to 700°C at a cooling rate of 1.5°C / h, and obtaining a lanthanum-aluminum solution in the quartz tube; S3. Post-treatment: After the quartz tube cooled to 700°C in step S2 is taken out from the muffle furnace, it is inverted in a centrifuge and centrifuged for 2 min. Then, the quartz tube is taken out from the centrifuge after it cools to room temperature. The quartz tube is opened to take out the lanthanum aluminum single crystal with a metallic luster, and the lanthanum aluminum single crystal is soaked in a diluted sodium hydroxide solution to remove impurities on its surface to obtain a high-quality lanthanum aluminum single crystal, which is recorded as sample 5.

[0049] The samples in the examples were characterized and tested, and the results were as follows: The sample 1 prepared in Example 1 was ground into powder and subjected to powder X-ray diffraction analysis. The results are as follows: Figure 1 The diffraction curve marked as experimental result in the figure represents the XRD test result of sample 1 in Example 1, and the diffraction curve marked as theoretical result in the figure represents the La3Al 11 XRD diffraction curve of Figure 1 It can be observed that the XRD characteristic peak position of sample 1 is consistent with that of La3Al 11 The peak positions of the samples are consistent, indicating that the sample 1 prepared in Example 1 is completely La3Al 11 phase, no other impurities.

[0050] The microscope image of sample 1 prepared in Example 1 is as follows Figure 2 As shown, sample 1 is prismatic in shape, about 5 mm in length, and has a complete crystal structure.

[0051] The samples 1-5 prepared in the examples were subjected to energy spectrum testing, and the results are shown in Table 1: Table 1 Energy spectrum test results of samples 1-5

[0052] The elemental energy spectrum (EDS) of sample 1 is as follows: Figure 3 As shown, Figure 3 The inset is a microscope image of the scanned area of ​​sample 1; Figure 3 It can be seen that the molar ratio of La to Al in the lanthanum aluminum single crystals obtained in each embodiment is between 3:(11-11.3), and the average molar ratio of La to Al is 3:11.18, which is very close to La3Al 11 The ideal value is 3:11, and there are no other impurities, and it is of very high quality.

[0053] The resistivity analysis test of the lanthanum aluminum single crystals prepared in Example 1 and Example 2 was performed to characterize the change of the resistivity of the lanthanum aluminum single crystals with temperature. The results are as follows: Figure 4 As shown, it can be seen that the lanthanum aluminum single crystals prepared in Example 1 and Example 2 both have metallic behavior. The resistivity of sample 1 prepared in Example 1 is 25.8 microohm·cm at 300 K, and the resistivity at absolute zero is 0.11 microohm·cm. It can be seen that the residual resistivity of sample 1 prepared in Example 1 is 235; while the resistivity of sample 2 prepared in Example 2 is 30.7 microohm·cm at 300 K, and the resistivity at absolute zero is 0.3 microohm·cm. It can be seen that the residual resistivity of sample 2 prepared in Example 2 is 103; the lanthanum aluminum single crystals prepared in Example 1 and Example 2 both have higher residual resistivity, and sample 1 has a higher residual resistivity than sample 2.

[0054] The magnetoresistance performance of the lanthanum aluminum single crystals prepared in Example 1 and Example 2 was tested to characterize the change of the magnetoresistance of the lanthanum aluminum single crystals under different magnetic fields at a temperature of 2 K with the magnetic field, as shown in FIG. Figure 5 As shown, it can be seen that both sample 1 and sample 2 have large magnetic resistance, the magnetic resistance of sample 1 reaches 8000%, and the magnetic resistance of sample 2 also reaches 3000%. Compared with sample 2, sample 1 has higher magnetic resistance.

[0055] The magnetic susceptibility test was performed on the lanthanum aluminum single crystals prepared in Example 1 and Example 2 to characterize the change of the magnetic susceptibility of the lanthanum aluminum single crystals under different magnetic fields at a temperature of 2 K with the magnetic field, as shown in FIG. Figure 6 As shown in Figure 2, it can be seen that the magnetic susceptibility of sample 1 at 2K shows obvious quantum oscillation behavior, while no quantum oscillation is observed in sample 2.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lanthanum aluminum single crystal, characterized in that: The molar ratio of lanthanum to aluminum in the lanthanum aluminum single crystal is 3:(11-11.8), the residual resistivity of the lanthanum aluminum single crystal is ≥100, and the magnetic resistance of the lanthanum aluminum single crystal at 2K is ≥3000%.

2. The lanthanum aluminum single crystal according to claim 1, characterized in that The length of the lanthanum aluminum single crystal is ≥0.1 mm; And / or, the residual resistivity of the lanthanum aluminum single crystal is ≥235; And / or, the magnetic resistance of the lanthanum aluminum single crystal at 2K is ≥8000%.

3. The lanthanum aluminum single crystal according to claim 1, characterized in that The magnetic susceptibility of the lanthanum aluminum single crystal at 2K shows a quantum oscillation effect.

4. A method for preparing a lanthanum aluminum single crystal as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Weighing raw materials: weighing lanthanum and aluminum under a protective atmosphere, mixing them to obtain a mixed raw material, wherein the molar ratio of the lanthanum to the aluminum is ≤1:10; S2, crystal growth: growing crystals from the mixed raw materials in step S1 under a vacuum environment, wherein the crystal growth is carried out at a holding temperature of 900-1200°C and a holding time of more than 1200 min, and after the holding is completed, the temperature is lowered at a cooling rate of ≤3.5°C / h to obtain a lanthanum aluminum solution; S3, post-processing: the lanthanum aluminum solution in step S2 is post-processed to obtain lanthanum aluminum single crystals.

5. The method for preparing lanthanum aluminum single crystal according to claim 4, characterized in that: The process of weighing the raw materials in step S1 is carried out in a glove box; And / or, the protective atmosphere in step S1 is at least one of nitrogen and argon; And / or, the molar ratio of the lanthanum to the aluminum in step S1 is 1:(11-15).

6. The method for preparing lanthanum aluminum single crystal according to claim 5, characterized in that: The specific process of step S1 is: in a glove box with a protective atmosphere, the lanthanum and the aluminum are weighed according to the molar ratio and placed in a container. After the lanthanum and the aluminum are evenly mixed, the outlet of the container is plugged with quartz wool and taken out from the glove box.

7. The method for preparing lanthanum aluminum single crystal according to claim 4, characterized in that: The time for the mixed raw material to rise from room temperature to the insulation temperature in step S2 is 800-1200 min; And / or, the cooling treatment in step S2 adopts one-step cooling or step-by-step cooling; And / or, the post-treatment in step S3 includes centrifugal treatment, quenching and flux removal.

8. The method for preparing lanthanum aluminum single crystal according to claim 7, characterized in that: The one-step cooling process is to reduce the temperature to 700-800°C at a cooling rate of ≤3.5°C / h; The step-by-step cooling process is to cool down to 900-950°C at a cooling rate of ≤3°C / h, then heat up to 1100-1150°C at a heating rate of 3-5°C / min, and then cool down to 700-800°C at a cooling rate of ≤3°C / h; And / or, the process of forming the vacuum environment in step S2 is: placing the mixed raw material in step S1 in a closed container with a protective atmosphere, extracting the protective gas in the closed container, and vacuum-sealing the mixed raw material in the closed container using a high-temperature flame in conjunction with a vacuum pump.

9. The method for preparing lanthanum aluminum single crystal according to claim 7, characterized in that: The temperature of the centrifugal treatment is 700-800°C; And / or, the rotation speed of the centrifugal treatment is ≥2500 r / min; And / or, the flux removal uses a sodium hydroxide solution.

10. Application of the lanthanum aluminum single crystal as described in any one of claims 1 to 3 in the fields of storage, sensor, quantum computing or quantum communication.

Citation Information

Patent Citations

  • Hexagonal system chromium antimonide single crystal capable of being used as alternating magnet material as well as preparation method and application of hexagonal system chromium antimonide single crystal

    CN118326520A

  • Rare-earth-ion-doped lanthanum scandate laser single-crystal optical fiber and preparation method thereof

    CN118957759A

  • METHODS OF FORMING A CRYSTALLINE Pr1-xCaxMnO3 (PCMO) MATERIAL AND METHODS OF FORMING SEMICONDUCTOR DEVICE STRUCTURES COMPRISING CRYSTALLINE PCMO

    US20120112151A1

  • Magnetoresistive structure

    WO2002009151A2